2015
DOI: 10.15226/2374-6858/2/1/00116
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Neurosurgical Psychomotor Performance: Role of Virtual Reality Simulators, Current and Future Potential

Abstract: Training surgeons is a dynamic process which is evolving towards more objective measures of assessing psychomotor technical skills. The current method for assessing neurosurgical trainees' technical skills is the in-training evaluation report (ITER). Despite the wide use of ITER in neurosurgical training programs, multiple authors have criticized its assessment validity. A number of other tools, designed and validated in the last two decades to assess the technical and cognitive skills of surgical procedures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In previous studies, our group has demonstrated how changes in the visual and tactile characteristics of simulated tumors influence bimanual psychomotor performance. 3,4,6 In the present study, altering the visual and tactile components of tumors resulted in well-defined 3D force pyramid patterns consistent with these results. The appearance of maximum force application crescents in the Q4 and Q3 quadrants was consistent in all tumors assessed, confirming the importance of the ergonomics of hand position during tumor resection.…”
Section: Force Pyramids Are Dependent On Tumor Visual and Haptic Charsupporting
confidence: 88%
See 3 more Smart Citations
“…In previous studies, our group has demonstrated how changes in the visual and tactile characteristics of simulated tumors influence bimanual psychomotor performance. 3,4,6 In the present study, altering the visual and tactile components of tumors resulted in well-defined 3D force pyramid patterns consistent with these results. The appearance of maximum force application crescents in the Q4 and Q3 quadrants was consistent in all tumors assessed, confirming the importance of the ergonomics of hand position during tumor resection.…”
Section: Force Pyramids Are Dependent On Tumor Visual and Haptic Charsupporting
confidence: 88%
“…The previously described NeuroTouch (now known as NeuroVR) platform was used to conduct this study. [1][2][3][4][5][6][7]10,11,14,16,20,26 Tumor removal was accomplished with a simulated virtual ultrasonic aspirator held in the participant's dominant hand (Fig. 1A).…”
Section: Neurovr Simulatormentioning
confidence: 99%
See 2 more Smart Citations
“…[35] Teaching in surgery is largely reliant on the apprenticeship model whereby the knowledge of a skill (know-how) is assumed to be learned through observation and graduated active responsibility in the operating room. [36] Therefore, a significant part of knowledge and skill acquisition also occurs through experiential learning. Trainees are often expected to learn a combination of complex skills to achieve expertise, without a comprehensive understanding of the individual components of holistic surgical competency.…”
Section: Benefits Of the Virtual Operative Assistantmentioning
confidence: 99%